Recent Demographic Changes in Different Agro-climatic Regions of Rajasthan - Malhotra, S P; Sen, Amal Kumar; Gupta, B S (Annals of Arid Zone, 2016)
An attempt has been made in the paper to establish the relationship between the spatial distribution of population along with its demographic characteristics as revealed in 1981 population census. The densily of population. the population growth rate in different agro-climatic regions are dealt with. Working population and their variation in different agro-climatic regions are then described. Proportion of main workers, marginal workers to total population in agro-climatic variation has also been added. The paper concludes with a note on the main findings of some demographic characteristics in agro-climatic regions. These are illustrated through three maps (1: 2,000,000 originally cartographed and sub. sequently reduced for publication) and three Tables.